Leading strategic transformation : the H-factor - Minbaeva, Dana (Emerald Publishing Limited, 2025)
In an age defined by volatility, complexity, and constant disruption, organisations face an imperative to adapt--or risk obsolescence. Yet despite the abundance of strategic models and change frameworks, many transformation efforts falter. The reason is not flawed strategy, but a persistent underestimation of the most critical enabler of change: human capital. Leading Strategic Transformation: The H-Factor challenges conventional approaches to change management, placing people--not processes--at the heart of successful transformation. Rooted in insights from strategic management, organisational behaviour, and complexity science, this incisive work introduces a dynamic, systems-based perspective on how organisations can thrive in uncertain, rapidly evolving environments. Rejecting linear planning and top-down control, the authors advocate for a shift toward complex adaptive systems thinking. Here, leadership is reimagined as the capacity to enable networks, foster agility, and mobilise human talent in service of long-term value creation. Combining theory with actionable insight, the book offers practical frameworks such as the Value Creation Pentad and the MELT model for human capital engagement and is essential reading for scholars and practitioners alike.